THE CRYSTAL STRUCTURE OF KAPUSTINITE NA5.5MN0.25ZR[SI6O16(OH 2]: A NEW MINERAL OF THE LOVOZERITE GROUP - Yamnova N.A.; Egorov-Tismenko Yu.K.; Pekov I.V.; Shchegol'kova L.V. (My University, 2004)
The NaZr silicate was discovered sixty years ago in Lovoserskij alkaline rock mass. It was called lovozerite. Crystal structures of more than 15 natural and synthetic lovezerites were determined by today. Zirconium, titanium, iron, calcium, manganese, sodium are the main elements of the lovozerites. New mineral of lovozerite group, kapustinite. Electronic-probe microanalysis has made it possible to find composition of the kapustinite. The composition is determined by the following formula: Na5.5Mo0.25Zr [Si6O16(OH)2]. X-ray diffraction analysis has been applied for determining the crystal structure. Results of the analysis have been presented.